Samuel Adedoyin - (service to Humanity) : a biography of Prince (DR.) Samuel Adedoyin - Sodimu, Yemi (Nigeria Royal Spring publications)
A biography of Samuel Adedoyin, who was a businessman, industrialist, philanthropist, humanity, and a visionary.
10/02/15, ijb 30/04/2019
Loans
Keywords: Samuel Adedoyin; Doyin Group; Businessmen; Business enterprises - Nigeria - History